2019
DOI: 10.1111/1756-185x.13713
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia, sleep disturbance and menopause: Is there a relationship? A literature review

Abstract: Introduction Fibromyalgia (FM) symptoms worsen in a significant portion of patients with the onset of menopause. Some patients report that their symptoms begin after menopause, suggesting a relationship between these entities. Sleep disturbance is a common condition in FM and menopause, and it is associated with chronic pain. Methods/Objectives Several electronic databases were searched, from the first available year to April 2018 to evaluate the publications that assessed the effects of menopause and sleep di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Chronic pain often leads to further psychiatric disorders such as anxiety and depression, which significantly affect the health-related quality of life [2][3][4]. Sleep disorders are the most common psychiatric disorders related to pain [5][6][7][8],…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain often leads to further psychiatric disorders such as anxiety and depression, which significantly affect the health-related quality of life [2][3][4]. Sleep disorders are the most common psychiatric disorders related to pain [5][6][7][8],…”
Section: Introductionmentioning
confidence: 99%
“…The study samples consisted of 150 women with a mean age of 42. 35 = 0.001, respectively). Besides, those with no history of depression had higher scores on the mental health subscale (52.4 ± 18.5 Vs. 44.4 ± 16.8, P-value = 0.007).…”
Section: Resultsmentioning
confidence: 90%
“…In other words, QoL has decreased with the onset of menopause. Studies have further shown that symptoms of premature or surgical menopausal hormone deficiency, as well as stress and mood swings, can lead to sleep disturbances and may be responsible for the onset or worsening of FMS-related symptoms and QoL (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Pain, and particularly chronic pain, is very common in the general population, affecting 30% of women [61,62]. At menopausal age, pain can easily affect a woman's behavior, lowering the time spent walking and moving in general.…”
Section: Discussionmentioning
confidence: 99%